FEEDING BEHAVIORS IN CHILDREN WITH AUTISM SPECTRUM DISORDER: A CROSS-SECTIONAL STUDY - Onal, Seda; Ucar, Aslı (My University, 2024)
This study aimed to examine the behavioral feeding problems in a sample of children with Autism Spectrum Disorder (ASD) and to examine the relationship of feeding problems to child sex and parents feelings about strategies to cope. This was a cross-sectional study of children aged 6-15 years with ASD. The parents or caregivers of the children/adolescents with ASD completed the following: sociodemographic information, questions about nutrition, and the Behavioral Pediatric Feeding Assessment Scale (BPFAS) for assessing the child’s behavioral feeding problems and parents’ feelings. Height and weight were used to calculate body mass index (BMI) percentiles. These percentiles for age and sex were used to define overweight and obesity (?85th and ?95th percentiles, respectively). The sample of the study consisted of 70 children with ASD (male: 49, female: 21), of which 45.8% were obese. The frequency of obesity in the males with ASD was higher than that in the females with ASD. BPFAS scores were higher in the females than in the males for all frequencies (total score, total problem score, child total score, child problem, parent total score, and parent problem). BPFAS total score was higher in the underweight children group (especially in the females). This study demonstrated that problematic feeding behaviors in children with ASD may differ according to sex. Behavioral interventions should be developed according to differences in feeding behavior.
Keywords: Autism spectrum disorder; sex differences; developmental disabilities; behavioral pediatric feeding assessment scale; feeding disorder